2021
DOI: 10.1111/anu.13236
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with Sporosarcina aquimarina MS4 enhances juvenile sea cucumber ( Apostichopus japonicus ) growth, immunity and disease resistance against Vibrio splendidus infection at low temperature

Abstract: Probiotics are important biological control products in the aquaculture of sea cucumber, but probiotics used specifically in low‐temperature environments are rare. The present study used treatment with low‐temperature‐resistant Sporosarcina aquimarina MS4 and investigated changes in growth, immunity, intestinal flora and immune‐related gene expression in sea cucumber at low water temperature (8°C). After 60 days of feeding, S. aquimarina MS4 significantly improved growth performance and immune enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…There are many published studies that reported that probiotics can improve the gut morphology and promote gut integrity in several aquatic animals, such as fingerlings great sturgeon ( H. huso ) ( Rastekenari et al, 2021 ), sea cucumber ( Apostichopus japonicus ) ( Zhou et al, 2021 ), Senegalese sole ( Solea senegalensis ) ( Batista et al, 2015 ), and tilapia ( O. niloticus ) ( Standen et al, 2013 , 2016 ). In this study, we found significant improvements in MT and MFH, indicating that the dietary supplementation of autochthonous probiotics ( B. pumilus SE5, Psychrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…There are many published studies that reported that probiotics can improve the gut morphology and promote gut integrity in several aquatic animals, such as fingerlings great sturgeon ( H. huso ) ( Rastekenari et al, 2021 ), sea cucumber ( Apostichopus japonicus ) ( Zhou et al, 2021 ), Senegalese sole ( Solea senegalensis ) ( Batista et al, 2015 ), and tilapia ( O. niloticus ) ( Standen et al, 2013 , 2016 ). In this study, we found significant improvements in MT and MFH, indicating that the dietary supplementation of autochthonous probiotics ( B. pumilus SE5, Psychrobacter sp.…”
Section: Discussionmentioning
confidence: 99%